THE THIRD INTERNATIONAL STROKE TRIAL (IST-3) MAIN RESULTS PART I: PRIMARY AND SECONDARY OUTCOMES AMONG 3035 PATIENTS RANDOMISED. (29th November 2012) - Venables, G; Sandercock, PAG; Lindley, R; Wardlaw, J; Dennis, M; Cohen, G
Abstract : Background: IST-3 seeks to improve the external validity and precision of the estimates of the overall treatment effects (efficacy and safety) of rtPA in acute ischaemic stroke, and determine whether a wider range of patients might benefit. Design: International, multi-centre, prospective, randomized, open, blinded endpoint trial of intravenous rtPA 0.9 mg/kg in acute ischaemic stroke. Patients were assessed and able to start treatment within 6 h of symptom onset, and brain imaging excluded intracranial haemorrhage and stroke mimics. Results: 3035 patients were recruited; 53% were aged >80 years. We will present analyses comparing the effect of rt-PA with control on, (a) events within 7 days: fatal and non-fatal symptomatic ICH; fatal and non-fatal neurological deterioration, attributed to swelling of initial ischaemic stroke; fatal and non-fatal neurological deterioration not attributable to brain swelling or symptomatic ICH; fatal and non-fatal recurrent ischaemic stroke; death from any cause within 7 days. (b) the primary outcome (proportion of patients alive and independent at 6 months as assessed by the Oxford Handicap Scale 0, 1, 2), (c) deaths from all causes within 6 months. Conclusion: The data from the trial will improve external validity and precision of the estimates of the overall treatment effects of iv rtPA in acute ischaemic stroke and provide new evidence on the balance of risk and benefit of iv rtPA among types of patients who do not clearly meet the terms of the current EU approval including those over 80 years of age.